Revitalizing primary health care - another utopian goal? - Marahatta, S B (Kathmandu University Medical Journal, 2012)
The quest for greater efficiency, fairness and responsiveness to the expectation of the people that system serve have brought about three generations of health system reforms in the twentieth century. The first generation saw the founding of national health care systems and extension to middle income nations of social insurance systems in the 1940s and 1950s. By the late 1960s the rising costs of hospital based care, its usage by better off, inaccessibility by the poor and rural population of even the most basic services heralded second generation reforms promoting primary health care as a means of achieving the affordable universal coverage. It included the best public health strategy that is prevention and the highest ethical principle of public health that is equity. It was expected the best system for reaching households with essential and affordable care, and the best route towards universal coverage. The primary health care approach though adopted universally did not materialize its notion of translating ethos of Health for All by 2000. Overall, primary health care movement by the end of 20th century became lifeless. Since the Declaration of Alma-Ata, fundamental changes have occurred affecting health service delivery, such as economic development and financing approaches, globalization of trade and knowledge, and the shift to privatization. This is the time to develop a new vision, taking into consideration the many changes affecting global health and the strategic developments in health of recent years. With this recognition, the third generation of reforms now underway in many countries is driven by the idea of responding more to demand, assuring access for the poor and emphasizing financing rather than just provision within the public sector. The key concern is: how to translate ethos of revitalizing in the reality. Otherwise the revitalizing concept will turn into utopian goal so like HFA by 2000 strategy.DOI: http://dx.doi.org/10.3126/kumj.v8i3.6225 Kathmandu Univ Med J 2010;8(3):341-51